Casais que não desejam ter filhos - Dias, Marília Rique de Souza Brito (2011)
In this study we will analyze an emerging phenomenon in Brazil and in the world, the couples who do not wish to have children. Our objective was to discuss their discourse about this theme having in mind the social imperative that orders them to have children. The dissertation constitutes itself by two articles: In the first, which is theoretical, we search, through a historical bibliographic pathway, to investigate the meaning of having children from the 16th century until our actual days. We found that within the centuries the speeches that were conducted to the family were transformed creating rules that had to be obeyed with the intention of giving, primarily, financial profit for the state. Nevertheless, it is clear that resistance movements always walked side by side with those rules having as objective to surpass them. The second article was a consequence from an empirical study with couples that did not haven children and also did not pretend to have. The results pointed out that these couples are in a constant struggle against the ruling speech. We concluded that it is possible that the couples who do not wish to have children become a part of the resistance movement, but, at the same time, it may constitute in relation to them, if they are inside and outside, a margin, but this margin is what delimits them and, in the difference and repletion enables the emergence of the new